Improvement of awareness and knowledge in colorectal cancer and its screening using online learning - Nurulhuda, M.H.; Norwati, D.; Aniza, A.A.; Harmy, M.Y. (2019)
Background and Aims: Colorectal cancer is the third most common cancer worldwide with 1.8 millon new cases in 2018. Colorectal cancer screening activities are found be be effective in reducing the mortality related to colorectal cancer. However, the uptake of these activities are still unsatisfactory, with one of the cause being low awareness and knowledge regarding the cancer and its screening. The aim of this study was to introduce a multimodality online course on colorectal cancer and its screening; and to measure its effectiveness in providing the awareness and knowledge in colorectal cancer and its screening. Methodology: An online course was designed for general public, incorporating essential knowledge regarding colorectal cancer and its screening using open courseware. Random group sampling was done to sample 80 undergraduate students. Knowledge and awareness on colorectal cancer and its screening was measured using a validated questionnaire pre- and post-exposure to the online course. Paired t-test in SPSS ver22 was used for analysis. Results: There was significant difference in Pre- and Post-exposure test on overall knowledge (p<0.001; CI: 14.23,18.78 , t=14.51), knowledge on colorectal cancer screening (p<0.001; CI: 3.04, 4.46 , t=10.62), and awareness (p=0.001; CI: 3.41,5.26 , t=9.39). Conclusion: Multimodality online learning is a useful tool to increase awareness and knowledge regarding colorectal cancer and its screening and is feasible to be used.